2023
DOI: 10.1123/smej.2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Careers and Publications Within the Sport Management Academy

Abstract: Sport management programs are essential pathways by which aspiring professionals in the sport industry achieve their university education. Although a substantial segment of sport management scholarship has focused on driving for higher rates of diversity, equity, and inclusion in the sport industry, less attention has been paid to the sport management academy. In this study, we examine the gender representation of full-time faculty positions, publications, and research methodologies in sport management. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Thus, "countable" research output tends to be attributed to men and teaching to women, indicating that people see women SMES professors as teachers and perceive the research achievements of women SMES professors to a lower extent than the achievements of men SMES professors (Mitchell & Martin, 2018). The gender differences in perceived power might be explained by the higher number of men in powerful, academic positions (Sailofsky et al, 2022). The results for competence and leadership qualities need further investigation.…”
Section: Perception Of Role Model Attributesmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, "countable" research output tends to be attributed to men and teaching to women, indicating that people see women SMES professors as teachers and perceive the research achievements of women SMES professors to a lower extent than the achievements of men SMES professors (Mitchell & Martin, 2018). The gender differences in perceived power might be explained by the higher number of men in powerful, academic positions (Sailofsky et al, 2022). The results for competence and leadership qualities need further investigation.…”
Section: Perception Of Role Model Attributesmentioning
confidence: 96%
“…This finding might be explained by the comparably high number of women professors in sport management. For example, the share of women faculty members at sport management departments in the United States is 42% and the share of full professors is 37.7% (Sailofsky et al, 2022). Furthermore, men who have a higher science attitude might be more interested in learning discipline-related skills, since they are more interested in scientific work.…”
Section: Choice Of Role Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the social sports sciences, sport economics and sport management are men-dominated disciplines, indicated by the low share of women coauthors in sports economics and sport management journals (Pitts et al, 2014;Gomez-Gonzalez et al, 2022). Previous studies reported an unequal gender distribution in sport management programs and faculties (e.g., Jones et al, 2008;Sailofsky et al, 2023). Furthermore, skills which are stereotypically attributed to men, e.g., mathematical, analytical, and statistical skills (Ginther and Kahn, 2004), are valued in economics.…”
Section: Role Fit and Gender Stereotypes Of Women And Men Academicsmentioning
confidence: 99%
“…However, for general economics, only 15% of full professors in the United States (US) are women, underlining that economics is a men-dominated discipline (Lundberg and Stearns, 2019 ). In sport management faculties in the US, 45.9% of assistant professors and 37.7% of full professors are women (Sailofsky et al, 2023 ), indicating that women's representation seems to decrease with hierarchical higher positions. No study indicates the number or share of women in sport sociology.…”
Section: Introductionmentioning
confidence: 99%